Knowledge-based integrated Production Management Model applied to automotive companies - Muniz Jr., Jorge [UNESP]; Batista Jr., Edgard Dias [UNESP]; Loureiro, Geilson (Inderscience Publishers, 2010)
This paper aims to examine the relevance of a production management model, in the shop-floor operations environment, that integrates the dimensions of production organisation (lean and mass production), work organisation (enriched and semi-autonomous groups) and knowledge management. A theoretical model has been applied to automotive companies to verify model adherence. Each of those dimensions has been described by factors. Shop-floor personnel interviews were conducted to confirm the factors relevance to that company. Results have shown that the model represented the reality of those companies concerning the researched dimensions. The factors allow managers to promote a favourable context for knowledge sharing. © 2010 Inderscience Enterprises Ltd.
Keywords: Automotive companies; Knowledge management; Production model; Production organisation; Tacit knowledge; Work organisation; Worker